Sangrovit® em dietas para tilápias do Nilo - Melo, Iury Walysson de Amorim (2016)
The phytogenic additives have shown positive results in chemicals replacement such as antibiotics in animal production, because it does not have cumulative effects on muscle and does not favor the selection of super-resistant bacteria. The experiment was conducted in two stages. The first stage aimed to evaluate the apparent digestibility coefficients (ADC) of protein, lipids, energy and mineral matter in 180 tilapia fish (40.0 ± 5.7g) fed with three diets (0; 100; and 200 mg kg-1) and four replications along 30 days. The second experiment aimed to determine the optimal inclusion of the additive through productive performance and by conducting hematologic, carcass centesimal composition analyses, as well as muscle and intestine morphometry. 240 fingerlings with average weight of 1.07 ± 0.07g were randomly distributed in 30 tanks of 138 liters, in recirculation system equipped with mechanical, biological filter and ultraviolet light to purify water for 60 days. The design was completely randomized with five treatments (0; 50; 100; 150 and 200 mg kg-1 additive) and six repetitions, each experimental unit consisting of eight fish. In both experiments the diets had approximately 38% crude protein and 3000 kcal of digestible energy. Growth performance (weight gain, feed conversion, daily weight gain, protein efficiency ratio, condition factor, survival, protein retention efficiency, visceral fat, hepatosomatic index, specific growth rate and lot uniformity), fish centesimal composition (moisture, crude protein, ether extract and ash), hematological indices, muscle fibers distribution and intestinal villus morphometry (villus height and epithelium thickness) were evaluated. The ADCs showed significant positive differences (p <0.05) between treatments. According to zootechnical, hematological, centesimal and histological parameters no differences were observed between treatments. We concluded that 100 kg-1 of Sangrovit® additive improves the apparent digestibility coeficient of protein, lipid, energy and mineral matter for tilapia.